2020
DOI: 10.1093/mnras/staa1528
|View full text |Cite
|
Sign up to set email alerts
|

K2-HERMES II. Planet-candidate properties from K2 Campaigns 1-13

Abstract: Accurate and precise radius estimates of transiting exoplanets are critical for understanding their compositions and formation mechanisms. To know the planet, we must know the host star in as much detail as possible. We present complete results for planet-candidate hosts from the K2-HERMES survey, which uses the HERMES multi-object spectrograph on the Anglo-Australian Telescope to obtain $R\sim 28\, 000$ spectra for more than 30 000 K2 stars. We present complete host-star parameters and planet-candidate radii … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 97 publications
0
10
0
Order By: Relevance
“…Analysis of asteroseismic and spectroscopic data together is key for GALAH+ DR3, and enables in-depth exploration of the structure and history of the Milky Way (e.g., Sharma et al 2016Sharma et al , 2019. The spectroscopic data also provide essential insights for the planet hosting stars identified in K2 data (Wittenmyer et al 2018(Wittenmyer et al , 2020.…”
Section: Target Selectionmentioning
confidence: 99%
“…Analysis of asteroseismic and spectroscopic data together is key for GALAH+ DR3, and enables in-depth exploration of the structure and history of the Milky Way (e.g., Sharma et al 2016Sharma et al , 2019. The spectroscopic data also provide essential insights for the planet hosting stars identified in K2 data (Wittenmyer et al 2018(Wittenmyer et al , 2020.…”
Section: Target Selectionmentioning
confidence: 99%
“…There are 18 K2 candidates that have problematic radii with 13 having been found to be false positives in previous work (Wittenmyer et al 2018(Wittenmyer et al , 2020…”
Section: R E F I N I N G P L a N E Ta Ry S Y S T E M Smentioning
confidence: 96%
“…Crossfield et al (2018) then independently identified K2-199 b and c as planet candidates in the C17 photometry. Recently, Wittenmyer et al (2020) reported updated semimajor axis and radius measurements for the three planets using stellar properties from observations with the High Efficiency and Resolution Multi-Element Spectrograph on the Anglo-Australian Telescope (Simpson et al 2016). In Section 2.5, we highlight the improvement to the precision of the planet orbital periods and mid-transit times by including both campaigns of photometry in our analysis.…”
Section: K2-182 and K2-199 Photometrymentioning
confidence: 99%